English Teachers’ Performance Evaluation as a Means for Their Professional Developments - Imelda Woa Wene; Retno Muljani (Universitas Jambi, Indonesia, 2020)
The study aimed to reveal how the teacher performance evaluation methods implemented by a private Catholic senior high school in Malang, East Java facilitated its English teachers towards their professional developments. This study employed a case study approach. The data from the participants - three senior English language teachers, two students, the school principal, vice principal, the head of Human Resources Development Section and supervisor from foundation were collected through semi-structured interviews. All data were analyzed qualitatively. The results revealed that the school employed five evaluation methods, namely, evaluation by students, self-evaluation, and evaluation by peers, evaluation by superior and supervision. The methods employed by the school provided positive impacts on the English teachers’ professional development, although the results of the evaluations did not serve as the main guideline for the school to include the teachers in development activities. The school carried out evaluation to ensure its teacher performance standard and the instruments to conduct the evaluation were always reviewed and adjusted to school culture and authentic conditions. The researchers suggest that the teachers should have their initiatives and build their agency to develop themselves professionally.